Evaluation of serum anti-pertussis toxin IgA antibodies for the diagnosis of Bordetella pertussis infection in young children - Zhiyun Chen; Xiaoguai Liu; Yuxiao Zhang; Xiaokang Peng; Nan Zhang; Ning Chen; Yarong Li; Qiushui He (Elsevier, 2023)
Background: The determination of serum anti-pertussis toxin (PT) IgG antibodies is recommended for the diagnosis and surveillance of pertussis. However, the diagnostic power of anti-PT IgG can be hampered by possible interference from previous vaccinations. We aim to assess if anti-PT IgA antibodies can be well induced by Bordetella pertussis (B. pertussis) infections in children, and their capacity to improve pertussis serodiagnosis. Methods: Serum samples from 172 hospitalized children younger than 10 years old with confirmed pertussis were tested. Pertussis was confirmed by culture, PCR and/or serology. Anti-PT IgA antibodies were determined with commercial ELISA kits. Results: Sixty-four (37.2 %) subjects had anti-PT IgA antibodies greater than or equal to 15 IU/ml, and 52 (30.2 %) of them had anti-PT IgA antibodies greater than or equal to 20 IU/ml. No children with negative anti-PT IgG (less than 40 IU/ml) were observed to have anti-PT IgA antibodies greater than or equal to 15 IU/ml. Of patients younger than one year of age, about 50 % had an IgA antibody response. Moreover, the proportion of subjects with anti-PT IgA antibodies greater than or equal to 15 IU/ml among PCR negative subjects was significantly higher than that among PCR positive subjects (76.9 % vs 35.5 %). Conclusions: The determination of anti-PT IgA antibodies does not seem to have added value for the serodiagnosis of pertussis in children older than one year of age. However, for infants, determination of serum anti-PT IgA antibodies appears to be useful for the diagnosis of pertussis especially when PCR and culture are negative. The results should be interpreted with caution as the number of subjects included in this study was limited.